PENYEBAB MINIMNYA KETERWAKILAN CALEG PEREMPUAN DI DPRD KABUPATEN SIJUNJUNG PERIODE 2019-2024 - Riyanda, Riko; Arman, Zuhdi; Anggela, Riri (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2022)
Based on data from The Sijunjung Regency Statistics Agency in 2020, the total female population is 115,191 residents out of a total of 235,045 residents of sijunjung regency or around 49,01 percent. This large number is not accompanied by the large number of famale council members in The Sijunjung Regency DPRD, but in fact the womens representation is minimal. The existence of an affirmative action policy does not necessarily make the women able to fulfill the 30% quota for representation in parliament. This study aims to explain the causes of the lack of representation of women candidates in The Sijunjung Regency DPRD for the 2019-2024 period. Methods of data collection is done by interview and documentation, informant selection technique with purposive sampling. The results of this study: (1) The lack of representation of women is due to women having problems in their ability, credibility and accessibility that have not been fully tested in their electoral districts (2) From the recruitment and regeneration carried out by political parties, it is more instant without being planned with the maximum which results in male candidates men are more dominant in grabbing the attention of the people in their constituencies, (3) female candidates are also less creative in getting people’s votes, (4) female candidates do not have a special strategy in attracting public votes like the male candidates who are elected.